2006
DOI: 10.1530/eje.1.02265
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and risk of type 2 diabetes, abdominal obesity and hypertension among Chinese adults

Abstract: Objective: To investigate the association between birth weight and risk of type 2 diabetes, abdominal obesity and hypertension among Chinese adults. Research methods and procedures: Nine hundred and seventy-three individuals from a population-based cross-sectional survey for the prevalence of type 2 diabetes conducted in Shanghai in 2002 were enrolled and followed up to 2004 with yearly examination. Birth weight was classified into four categories: !2500, 2500-2999, 3000-3499 and R3500 g. Results: In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
89
2
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 31 publications
8
89
2
9
Order By: Relevance
“…35,47,48 Although most fetal origins of adult disease studies were conducted in white populations, an increasing number of studies from China and India confirm the influence of low BW on adult blood pressure, glucose metabolism, and other cardiovascular risk factors. [49][50][51][52] Mortality and morbidity from coronary artery disease, diabetes mellitus, and chronic kidney disease are expected to increase by 200% to 400% in developing countries during the next 30 years because of increased longevity and adverse…”
Section: Discussionmentioning
confidence: 99%
“…35,47,48 Although most fetal origins of adult disease studies were conducted in white populations, an increasing number of studies from China and India confirm the influence of low BW on adult blood pressure, glucose metabolism, and other cardiovascular risk factors. [49][50][51][52] Mortality and morbidity from coronary artery disease, diabetes mellitus, and chronic kidney disease are expected to increase by 200% to 400% in developing countries during the next 30 years because of increased longevity and adverse…”
Section: Discussionmentioning
confidence: 99%
“…Further, traits in one trajectory might interact with traits in another trajectory to influence cardiometabolic health. Considering birth weight and adulthood waist circumference, for example, risk for type two diabetes is greatest for individuals born light who went on to develop large waist lines (Tian et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…7,9 Empirical evidence has shown that obesity risks typically increase linearly with weight at birth: high birthweight infants are at higher risk of long-term overweight; 8 evidence of higher risk of obesity at the low end of the birthweight distribution has been less frequently observed. 8,[10][11][12] High birthweight may be associated with later obesity due to larger size stemming from high levels of lean mass, 13,14 while low birthweight may be associated with higher central adiposity. [15][16][17][18] Studies have also indicated that postnatal growth during the first 1-2 years of life may be positively associated with subsequent obesity in childhood, adolescence and adulthood, as obesity risks, both in terms of body mass index (BMI) and adverse body composition, are higher for those who experienced rapid postnatal weight gain.…”
Section: Introductionmentioning
confidence: 99%